2019
DOI: 10.18178/ijiet.2019.9.7.1246
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Digital Technology for Better Learning and Education: A Systematic Literature Review

Abstract: He completed his bachelor of science in agriculture and the master in agricultural extension education from Bangladesh Agricultural University. He also completed MBA from commonwealth of learning. He also completed two diplomas in banking and Islamic banking. His research interest includes resilience, disaster management, livelihood and climate changes and education economy. He has published couple of scientific articles and one book on Poverty of Island Char Dwellers in Bangladesh. He is a member of several p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 38 publications
3
73
0
7
Order By: Relevance
“…This content has been developed in vocational training, specifically in the Higher Level Training Cycle of Dietetics, in the Spanish context. After analyzing the results obtained, it can be indicated that the pedagogical method based on the use of technological resources generates better learning and better acquisition of the content, as was obtained in recent studies [ 47 , 48 ]. That is, the application of an active and innovative teaching method leads to substantial improvements in the learning of students of vocational training in the Higher Degree of Dietetics.…”
Section: Discussionmentioning
confidence: 83%
“…This content has been developed in vocational training, specifically in the Higher Level Training Cycle of Dietetics, in the Spanish context. After analyzing the results obtained, it can be indicated that the pedagogical method based on the use of technological resources generates better learning and better acquisition of the content, as was obtained in recent studies [ 47 , 48 ]. That is, the application of an active and innovative teaching method leads to substantial improvements in the learning of students of vocational training in the Higher Degree of Dietetics.…”
Section: Discussionmentioning
confidence: 83%
“…Construction 4.0 (C4.0) and Industry 4.0 (I4.0) were described by [12,13] as the proliferation of state-of-the-art equipment and tools in carrying out operations predominantly being carried out in the past engaging old methods. It involves the deployment and application of digital technology to integrate the functional components of construction operation and processes.…”
Section: Understanding the I40 And C40 Conceptsmentioning
confidence: 99%
“…Therefore, this study aims to achieve an inclusive pathway towards the sustainable innovation and inclusive technological developments that are necessary to support sustainable design and inclusive industrial development goals 9 and 11 [13][14][15]. The objectives of goals 9 and 11 include achieving sustainable infrastructure, resilient structures and inclusive technological developments [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when the students are actively engaged, there is greater chance of grasping the lesson. The recent study [13] that looked at how to most effectively integrate digital technology into educational setting revealed a consensus that particular strategies can promote significant improvement in student learning.…”
Section: Interactive Engagementmentioning
confidence: 99%